2020
DOI: 10.21608/besps.2019.14726.1027
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide generation protects against renal ischemia/reperfusion-induced cardiac hypertrophy and arrhythmia via amelioration of connexin- 43 expression and opening of KATP channels

Abstract: Hydrogen sulfide has been recently studied as a potential treatment for many cardiovascular disorders. Here, we describe its role in I/R-induced cardiac hypertrophy and arrhythmia model. Thirty six male Sprague Dawley rats were used in this study. Rats were randomly divided into 6 groups, G 1(n = 6/group): control negative: received saline, G2, I/R rats, (I/R, n = 6), after right nephrectomy, the rats were subjected to left kidney ischemia for 45 minutes followed by reperfusion:,G3, I/R rats in which rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…Similarly, a recent study indicated that H 2 S-induced elevation of miR-133a results in the downstream regulation of the Ca 2+ /calcineurin/nuclear factors of activated T-cells pathway [ 162 ]. Furthermore, the treatment of a CH-induced rat model with NaHS markedly restores ventricular function by reducing the expression of connexin-43 and activating K ATP channels [ 163 ]. A recent study further shows that treatment with SG1002 can prevent Hcy-induced hypertrophy in CBS +/- mice and improve cardiac function by reducing MMP activity and TGF-β activation [ 164 ].…”
Section: H 2 S and Cvdsmentioning
confidence: 99%
“…Similarly, a recent study indicated that H 2 S-induced elevation of miR-133a results in the downstream regulation of the Ca 2+ /calcineurin/nuclear factors of activated T-cells pathway [ 162 ]. Furthermore, the treatment of a CH-induced rat model with NaHS markedly restores ventricular function by reducing the expression of connexin-43 and activating K ATP channels [ 163 ]. A recent study further shows that treatment with SG1002 can prevent Hcy-induced hypertrophy in CBS +/- mice and improve cardiac function by reducing MMP activity and TGF-β activation [ 164 ].…”
Section: H 2 S and Cvdsmentioning
confidence: 99%